Integration Approaches of UPLC-Q-Exactive Orbitrap-MS/MS, Network Pharmacology Molecular Docking, and Molecular Dynamics to Explore the Effective Constituents and Potential Mechanisms of S. vaniniiporus vaninii against Tumor - Li, Wen-long; Wang, Pei-lu; Xu, Yan; Shan, Meng-yi; Cheng, Gang; Sheng, Yun-jie; Liu, Kao-hua; He, Bing-qian; Shi, Qi; Li, Hua-qiang; Meng, Xiong-yu; Qin, Lu-ping (Current Pharmaceutical Design, 2025)
BackgroundS. vaninii, a well-established traditional Chinese medicine with potent pharmacological effects against cancer, lacks clarity regarding its mechanism of action.ObjectiveTo elucidate the bioactive components in S. vaninii and to elucidate their potential anticancer mechanisms.MethodsFirstly, the chemical composition of S. vaninii was characterized using UPLC-Q-Exactive Orbitrap-MS/MS technique. Subsequently, bioinformatics-related techniques were employed to elucidate the bioactive components and potential mechanisms of S. vaninii anti-tumor based on the identified chemical constituents. Finally, molecular dynamics simulation was conducted to validate the obtained results.ResultsOur findings revealed the characterization of 226 constituents from S. vaninii including 30 flavonoids, 27 carbohydrates and glycosides, 26 amino acids, peptides and their derivatives, 18 phenylpropanoids, 13terpenes, 12 phenols, 6 organic acids and its derivatives, 4 alkaloids, etc. Subsequently, 195 key tumor-related active compounds were identified and established in the Drug-Compound-Target-Disease network. The PPI network screened out 85 key targets (TP53, STAT3, EGFR, GAPDH, BCL2, AKT1, CASP3, mTOR, JUN, and TNF) in tumors. Furthermore, functional enrichment analyses using GO and KEGG pathways highlighted the involvement of PI3K-Akt signaling pathways in S. vaninii's anti-tumor effects. Finally, the top ten significant bioactive constituents were selected as key targets for molecular docking studies which revealed Alpinetin, Galangin, and 4',5-Dihydroxyflavone as potential core compounds targeting mTOR, EGFR, and AKT1 respectively; these complexes were further assessed for stability through MD simulations.ConclusionThis study provides insights into the potential active compounds, target proteins, and signaling pathways underlying the clinical application of S. vaninii in treating tumors.
Keywords: UPLC-Q-Exactive orbitrap-MS/MS